DAMPAK PELATIHAN KIT IPA TERHADAP PENGEMBANGAN KEMAMPUAN SAINTIFIK GURU SEKOLAH DASAR DI MAGELANG - Sukmarani, Dhuta; Alawiyah, Ela Minchah Laila; Mahardika, Astuti (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2016)
Science in Elementary School aims to enable students to understand science concepts, process skills, have an interest in studyingthe natural surroundings, the scientific attitude and be able to apply the concepts of science. Submission of science just by generallecturing and examination tend to make students bored and mastery of the science by the students less than the maximum.Submission of science by providing hands on experience to students through the use of KIT is one alternative in science learning.The aim of this research is to know how the impact of science KIT training towards the development of scientific capabilitiesfor elementary school teachers in Magelang. This pre-experimental study using a sample of 14 teachers from 12 primary schoolsin Magelang. Data collection techniques used in this research is through questionnaires, while data analysis using descriptivestatistics of the questionnaire. The conclusion that can be drawn from this study is that science KIT training can provide apositive impact on the development of the scientific capabilities of the teachers.